Previdências dos trabalhadores dos setores público e privado e desigualdade no Brasil - Marcelo Medeiros; Pedro H. G. F. de Souza (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The study examines a particular set of institutional determinants of inequality, the public pensions. It tests the hypothesis that different rules regarding a maximum limit for the value of benefits in the pension subsystem of public and private sector workers makes the system as a whole regressive and contributes disproportionately to inequality in Brazil. Using a factor decomposition of the Gini coefficient of the distribution of family per capita income, as measured by POF 2008-2009 it concludes that the State reproduces pre-existing inequalities when it differentiates rules for public and private sector workers. Due to this differentiation of rules, the higher value pensions of less than 1% of the population contributes to 4% of total inequality.
Keywords: H24; H55; I38; 330; income inequality; public pensions; INSS; RPPS; RGPS